Pengaruh Perbandingan Sosial, Fear Of Missing Out (FOMO), Ketangguhan Mental, Dan Social Media Jealousy Terhadap Niat Pembelian Produk Fashion Pada Pengguna Aktif Media Sosial Generasi Z Di Indonesia - Mochamad apriliandi; Dzuklifi Dzuklifi; Ria Aulia (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study examines the influence of social comparison, fear of missing out (FOMO), and mental toughness on fashion product purchase intention among active social media users of Generation Z in Indonesia, with social media jealousy included as an additional predictor. A quantitative associative approach was employed, using an online questionnaire distributed to 61 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with IBM SPSS Statistics version 27. The instrument was found to be valid and reliable, and the classical assumption tests indicated that the regression model was normally distributed and free from multicollinearity and heteroscedasticity. The F-test showed that the independent variables jointly had a significant effect on purchase intention (F = 5.792; sig. = 0.002), with an R² of 0.237, indicating that the model explained 23.7% of the variance in purchase intention. Partially, mental toughness was found to have a significant effect on purchase intention, while social comparison and FOMO did not show a statistically significant partial effect. These findings suggest that psychological resilience plays a more consistent role than social pressure factors in shaping Generation Z's fashion purchase intention, and that other variables outside the model likely contribute substantially to this behavior.